Association of Primary Care Providers’ Beliefs of Statins for Primary Prevention and Statin Prescription - Clough, Jeffrey D. (J Am Heart Assoc, 2019)
BACKGROUND: The 2013 American College of Cardiology/American Heart Association Cholesterol Treatment Guideline increased the number of primary prevention patients eligible for statin therapy, yet uptake of these guidelines has been modest. Little is known of how primary care provider (PCP) beliefs influence statin prescription. METHODS AND RESULTS: We surveyed 164 PCPs from a community‐based North Carolina network in 2017 about statin therapy. We evaluated statin initiation among the PCPs’ statin‐eligible patients between 2014 and 2015 without a previous prescription. Seventy‐two PCPs (43.9%) completed the survey. The median estimate of the relative risk reduction for high‐intensity statins was 45% (interquartile range, 25%–50%). A minority of providers (27.8%) believed statins caused diabetes mellitus, and only 16.7% reported always/very often discussing this with patients. Most PCPs (97.2%) believed that statins cause myopathy, and 72.3% reported always/very often discussing this with patients. Most (77.7%) reported always/very often using the 10‐year atherosclerotic cardiovascular disease risk calculator, although many reported that in most cases other risk factors or patient preferences influenced prescribing (59.8% and 43.1%, respectively). Of 6172 statin‐eligible patients, 22.3% received a prescription for a moderate‐ or high‐intensity statin at follow‐up. Providers reporting greater reliance on risk factors beyond atherosclerotic cardiovascular disease risk were less likely to prescribe statins. CONCLUSIONS: Although beliefs and approaches to statin discussions vary among community PCPs, new prescription rates are low and minimally associated with those beliefs. These results highlight the complexity of increasing statin prescriptions for primary prevention and suggest that strategies to facilitate standardized discussions and to address external influences on patient beliefs warrant future study.